An Exploring of Academic Social Networks by ArnetMiner System - ชัยวนารมย์ ปวีณา (KKU Science Journal, 2012)
ArnetMiner system has been developed to search and mine for academic social networks. The main services of the ArnetMiner system are browsing and searching the researcher information in Computer Science and the related fields. This system includes a personal profile, pairwise relationship between a pair of researchers, and community relationship among the related researchers. This paper addresses several key issues of the ArnetMiner system: 1) history of the system, 2) architecture, 3) available services for end users and developers, and 4) many potential future directions of the system.